2004
DOI: 10.1021/bm030079a
|View full text |Cite
|
Sign up to set email alerts
|

NMR Imaging of the Diffusion of Water at 37 °C into Poly(2-hydroxyethyl methacrylate) Containing Aspirin or Vitamin B12

Abstract: The ingress of water into poly(2-hydroxyethyl methacrylate), PHEMA, loaded with either one of two model drugs, vitamin B(12) or aspirin, was studied at 37 degrees C using three-dimensional NMR imaging. PHEMA was loaded with 5 and 10 wt % of the drugs. From the imaging profiles, it was observed that incorporation of vitamin B(12) into PHEMA resulted in enhanced crack formation on sorption of water and the crack healing behind the diffusion front was slower than for PHEMA without added drug. This was accounted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The extent of crack formation observed in Figures 2a and 3a is much greater than that found by Ghi et al 17 for these two copolymers without any drugs present, and mirrors the observations made for PHEMA in the presence of vitamin B 12 20. This enhancement of the cracking has been attributed to an ‘anti‐plasticization’ effect of vitamin B 12 on PHEMA and the copolymers rich in HEMA 21.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The extent of crack formation observed in Figures 2a and 3a is much greater than that found by Ghi et al 17 for these two copolymers without any drugs present, and mirrors the observations made for PHEMA in the presence of vitamin B 12 20. This enhancement of the cracking has been attributed to an ‘anti‐plasticization’ effect of vitamin B 12 on PHEMA and the copolymers rich in HEMA 21.…”
Section: Resultssupporting
confidence: 76%
“…MRI studies of the copolymers rich in HEMA, carried out by Ghi et al 15, 17 showed that cracks develop at the interface between the rubbery outer annulus and the glassy core during swelling, and that these cracks are ‘repaired’ behind the diffusion front when the glass transition temperature ( T g ) of the water‐plasticized matrix drops below the temperature of measurement. More recently, Chowdhury et al 20 have reported similar studies on poly(HEMA) (PHEMA) in the presence of the added drugs aspirin and vitamin B 12 , in which they showed that aspirin plasticized the PHEMA and the extent of interface crack formation in the polymer was reduced, although vitamin B 12 had the opposite effect.…”
Section: Introductionmentioning
confidence: 91%
“…The effective diffusion coefficients we estimated were consistent with the observed delay of staining in central portions of the specimens. The one-dimensional model used here (Equation 1) potentially could be improved by using a three-dimensional model having cylindrical geometry 30 or with additional dedicated experiments 33 beyond the scope of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of solvent uptake, only the molecules of solvent contribute to the signal. However, contrast of the image could be adjusted by any factors measurable by NMR, such as changes in concentration Chowdhury, Hill, & Whittaker, 2004a;Chowdhury, Hill, Whittaker, Braden, & Patel, 2004b;Fyfe & Blazek, 1997;Thérien-Aubin, Baille, Zhu, & Marchessault, 2005;Thérien-Aubin & Zhu, 2006;Thérien-Aubin, Zhu, Ravenelle, & Marchessault, 2008), relaxation times (Chowdhury et al, 2004b;Fyfe & Blazek, 1997;Rajabi-Siahboomi, Bowtell, Mansfield, Davies, & Melia, 1996), or self-diffusion coefficients Kojima & Nakagami, 2002;Rajabi-Siahboomi et al, 1996;Thérien-Aubin et al, 2008;Tritt-Goc, Kowalczuk, & Pislewski, 2003). NMR imaging is widely used to follow water uptake and moisture diffusion and to assess the water distribution in a system in different polymeric and starch-based systems (Hopkinson, Jones, Black, Lane, & McDonald, 1997;Horigane, Takahashi, Maruyama, Ohtsubo, & Yoshida, 2006b;Horigane et al, 2006a;Kasai, Lewis, Ayabe, Hatae, & Fyfe, 2007;Russo et al, 2007;Ziegler, MacMillan, & Balcom, 2003).…”
Section: Nmr Imaging Of Chemically Modified High Amylose Starch Contrmentioning
confidence: 99%